TRANSFORMATION OF HIGHER EDUCATION HUMAN RESOURCE DEVELOPMENT: BUILDING DIGITAL COMPETENCIES IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Marlina, Marlina; Jayanti, Prita Steady; Thama, Tuti Adhi; Nuraini, Intan; Muljadi, Muljadi (Univesitas Muhammadiyah Tangerang, 2025)
Digital transformation in higher education is urgent in the 4.0 era, with the use of technologies such as AI, IoT and Big Data analytics. This study examines the strategy of the University of Muhammadiyah Tangerang in developing digitally competent human resources. This research uses a qualitative design based on case studies, involving bibliometric analysis, interviews with policy makers, lecturers, staff, as well as policy analysis and observation of human resource development practices. The results of the study show the urgent need for digital competencies in higher education. UMT has designed strategic initiatives such as technology-based training, the use of LMS, and collaboration with technology companies. However, the challenges of budget constraints, disparities in digital capabilities and resistance to new technologies remain. Great opportunities come with affordable technology developments and national policy support. His recommendations strengthen technology-based policies, the integration of digital elements of the curriculum, and strategic partnerships with industry. This step supports UMT's vision to contribute to the development of sustainable human resources in future education. Obstacles include budget constraints and resistance to the adoption of new technologies.